Ecological consciousness as the basis for person's ecological culture - Виговський, Л.; Виговська, Т. (Київський національний університет імені Тараса Шевченка, 2019)
The article shows that in the conditions of global ecological crisis Homo sapiens as a species can only survive if the problem of restoring historically lost balance of relations in the general system of "human being – natural environment" is resolved as soon as possible. We argue that such a process requires, first and foremost, an appropriate reorientation of the humanity's worldview with respect to the nature and formation of environmental consciousness in members of the human community based on such principles. It is proved that in the system of ecological consciousness the worldview plays a systematic role, because it gives a person the answer to the question about the main values and priorities in human life, provides appropriate ideological justification of thoughts and actions that meet the ecological needs of people and communities. It is emphasized that, in such a situation, the preservation and restoration of the environment, which forms the need for ecological activity, becomes a sense of human life. The role of historical types of worldview (mythological, religious, scientific) in shaping the attitude of a person to nature is shown. We also show that the characteristics of the main levels of formation of the person's ecological consciousness is, at the same time, the characteristics of their ecological maturity. This is due to the fact that the typological groups reflect the degree of perception of environmental ideas and the adoption of environmental principles with subsequent implementation in environmental activities. We show that the levels of environmental consciousness can be classified as naive-realistic, everyday-empirical, and conscious-theoretical. The naive-realistic level of maturity of environmental consciousness is characteristic of people who act as natural environmentalists in their lives. The everyday-empirical level is characterized by the existence (in the rational and emotional areas) of a negative attitude to environmental problems. The conscioustheoretical level of such consciousness is characterized by informed and active attitude to environmental problems. It is emphasized that in the process of forming an ecological worldview, there is a need to move from the dominance of the environmental paradigm to the dominance of the ideological, moral and ethical paradigms.

Наголошується, що в умовах глобальної екологічної кризи актуальною є проблема формування і підвищення зрілості екологічної свідомості особистості. Підкреслюється, що в системі такої свідомості саме світогляд виконує системоформувальну функцію, оскільки дає людині відповідь на запитання про сенс життя в контексті екологічної діяльності. Розкривається роль історичних типів світогляду (міфологічний, релігійний, науковий) у контексті такої діяльності, Аргументується положення про те, що характеристика основних рівнів сформованості екологічної свідомості індивіда одночасно є і характеристикою рівнів її екологічної зрілості. Це зумовлюється тим, що типологічні групи відображають ступінь сприйняття екологічних ідей та засвоєння екологічних принципів з наступною реалізацією в екологічній діяльності. Доводиться, що можна виокремити три основних рівні екологічної зрілості свідомості особистості: наївно-реалістичний, буденно-емпіричний та свідомо-теоретичний. Наївно-реалістичний рівень зрілості екологічної свідомості притаманний людям, які в житті ведуть себе як стихійні екологи. Показується, що для буденно-емпіричного рівня характерна відсутність (у раціональній та емоційній сфері) негативного ставлення до екологічних проблем. Доводиться, що для свідомо-теоретичного рівня такої свідомості особистості характерне усвідомлене й активне ставлення до розв'язання екологічних проблем.
Екологічна свідомість як основа екологічної культури особистості
Keywords: worldview; ecology; consciousness; environmental consciousness; mythological consciousness; scientific worldview; real-world outlook; levels of ecological maturity in person's consciousness; світогляд; екологія; свідомість; екологічна свідомість; міфологічний світогляд; релігійний світогляд; науковий світогляд; рівні екологічної зрілості свідомості людини